KARAKTERISTIK MODA ANGKUTAN BARANG DI LINTAS JALUR PANTAI UTARA JAWA (OBSERVASI PADA WILAYAH EKS KARESIDENAN PEKALONGAN) - , JOOPIE KELANA SOESILO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
By looking at the phenomenon of the rapid technological advances in the field of road transport, there is a significant difference between the geometric conditions are based on vehicle dimensions plan set by the Directorate General of Highways is in terms of the vehicle is a vehicle that elected dimensional elements technical vehicle, dimensions and operating characteristics of the vehicle is used to design the geometry of the road so that they meet the vehicle movement plan (Kusnandar, 2005) with the condition of the vehicle dimensions currently experiencing a significant change, so there is a result in the decline of road safety that need to be done changes or adapted to the real conditions of the moment. The study was conducted on roads in the North Coast at Pekalongan area, covering vehicle dimensions, the service life and commodities transported. To determine the limit of the vehicle dimensions refer to the regulations. Commodities daily necessities are transported by cargo of freight transport, freight transport modes 53.59% traveled more than 200 kilometers, the largest Maximum Turning Radius contained on Semi Trailer with axis configuration 1.22-22 and 1.22-222 is 13,450 millimeters, Road Services by Age Survey Results / observations for directions Jakarta (West) for 6.8 years and the direction of Semarang (East) of 7.13 years